The Utilization of Smart Price Application Based Android - Very Karnadi; Sunarsan Sitohang (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The increasing purchasing power of consumers in purchasing products at large stores nowadays often displays only samples of goods. So that customers often feel confused to see in detail the form of goods to be purchased, so that customers often feel confused and seek employees to ask questions about the details of the item to be purchased. The main objective of this research is to create, design and build a front end database server that is useful for consumers in increasing customer convenience in shopping at the mini-market retail business. The use of the application that will be made is in the form of a barcode scanning feature wherein each individual there is information in the form of item details such as id, name, dimensions, quantity, colour, price, and images of goods obtained from the scanned items that have been entered into their respective identities description of goods. The app also features a fast checkout feature. The use of this application can be searched using an internet application. It can be accessed wherever the customer is because the cashier programming is directly connected to the web server provided by the supermarket.